From ballroom to dancesport : aesthetics, athletics, and body culture - Picart, Caroline Joan, 1966- (SUNY series on sport, culture, and social relations., 2006)
"Drawing on recent media portrayals and her own experience, author and dancer Caroline Joan S. Picart explores ballroom dancing and its more "sporty" equivalent, DanceSport, suggesting that they are reflective of larger social, political, and cultural tensions. The past several years have seen a resurgence in the popularity of ballroom dance as well as an increasing international anxiety over how and whether to transform ballroom into an Olympic sport. Writing as a participant-critic, Picart suggests that both are crucial sites where bodies are packaged as racialized, sexualized, nationalized, and classed objects. In addition, Picart argues, as the choreography, costuming, and genre of ballroom and DanceSport continue to evolve, these theatrical productions are aestheticized and constructed to encourage commercial appeal, using the narrative frame of the competitive melodrama to heighten audience interest."--Jacket